1979
DOI: 10.2170/jjphysiol.29.569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium on the Contractility of a Frog Cardiac Muscle in Relation to pH of External Solution

Abstract: In order to examine the pH dependency of Cd effects on cardiac muscle, the electrical and mechanical activities in the bullfrog heart were investigated in relation to various external pHs and concentrations of Cd. The amplitude and duration of the action potential or the spontaneously beating frequency in the atrium were not significantly affected during the 3-min administration of various concentrations of Cd in a range from pH 6 to 10, but the isotonic contraction at the end of the same period was greatly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Moreover, we observed that lowering the external pH altered neither the efficiency of Cd inhibition on Ij nor the affinity of Cd for the site. The present results might account for the increase in the negative inotropic effect of Cd in low pH solution reported by Horiuchi & Hayashi (1979), since low pH media is shown to reduce markedly the maximal Ca entry while the ability of Cd to block I~j is unchanged. This might also suggest that the blocking effect of H and Cd ions on Isj was additive.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, we observed that lowering the external pH altered neither the efficiency of Cd inhibition on Ij nor the affinity of Cd for the site. The present results might account for the increase in the negative inotropic effect of Cd in low pH solution reported by Horiuchi & Hayashi (1979), since low pH media is shown to reduce markedly the maximal Ca entry while the ability of Cd to block I~j is unchanged. This might also suggest that the blocking effect of H and Cd ions on Isj was additive.…”
Section: Discussionsupporting
confidence: 64%
“…Cd ions have been found to be a selective blocker of the slow inward current (Is;) in various species (Kostyuk et al, 1977;Lee & Tsien, 1982; Giles et al, 1983;Josephson et al, 1984;Gautier et al, 1987). In addition, H ions, known to depress ISi in heart muscle (Chesnais et al, 1975), have also been found to cause a dramatic enhancement of the negative inotropic effect of Cd in frog cardiac muscle mechanical activity (Horiuchi & Hayashi, 1979). These findings prompted us to investigate the combinative effect of H and Cd ions on Is; in frog cardiac tissue.…”
Section: Introductionmentioning
confidence: 99%